2003
DOI: 10.1136/bjsm.37.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Energy demands during a judo match and recovery

Abstract: Objective: To assess energy demand during a judo match and the kinetics of recovery by measuring the metabolites of the oxypurine cascade, lipolytic activity, and glycolytic pathway. Methods: Venous blood samples were taken from 16 national judoists (mean (SEM) age 18.4 (1.6) years), before (T 1 ) and three minutes (T 2 ), one hour (T 3 ), and 24 hours (T 4 ) after a match. A seven day diet record was used to evaluate nutrient intake. Results: Nutrient analysis indicated that these athletes followed a low carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
107
6
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 25 publications
17
107
6
17
Order By: Relevance
“…This is in line with research pointing to a relevant contribution of oxidative pathways, together with anaerobic metabolism, to the muscle energy output of a judo match and its recovery, 6 with elite judo players being powerful athletes but also having above-average endurance capacity. In fact, recent research showed higher frequency of the I allele and II genotype in the angiotensin-converting enzyme (ACE) gene (which theoretically would favor endurance performance) in elite Polish and Lithuanian judokas, suggesting that genetic predisposition for longer fighting is at least as important (if not more so) than genetic predispositions to speed or power.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This is in line with research pointing to a relevant contribution of oxidative pathways, together with anaerobic metabolism, to the muscle energy output of a judo match and its recovery, 6 with elite judo players being powerful athletes but also having above-average endurance capacity. In fact, recent research showed higher frequency of the I allele and II genotype in the angiotensin-converting enzyme (ACE) gene (which theoretically would favor endurance performance) in elite Polish and Lithuanian judokas, suggesting that genetic predisposition for longer fighting is at least as important (if not more so) than genetic predispositions to speed or power.…”
supporting
confidence: 56%
“…5 Thus, the mean duration of a men's match is ~7 minutes, 4 and, although anaerobic metabolism is thought to be the primary energy source for this sport (eg, with mean plasma lactate concentrations of ~12 mmol/L at the end of a match), aerobic pathways (involving carbohydrate, as well as lipid and protein, metabolism) are also involved. 6 Furthermore, although maximal aerobic capacity (VO 2max ) is not a discriminatory variable in competitive performance, it is a valuable one; judokas with higher VO 2max values might have an advantage in combats lasting the maximal 10-minute duration allowed. 5 We determined ACTN3 R577X genotype and allele frequencies in the majority of all-time-best Spanish judo male athletes (n = 111, current age range 18-75 y, 57.7% still active).…”
mentioning
confidence: 99%
“…This data was in line with the findings of Degoutte et al (Degoutte et al, 2003), who observed that lactate concentrations in blood were appeared to return to the baseline level within 24 hours. Also, in study conducted by Kantanista blood lactate decreased after the interruption of exercise (Kantanista et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…A typical high-level judo match lasts 3 minutes, with 20-to 30-second periods of activity and 5-10 seconds of interruption, while a significant portion of a match lasts 3-4 minutes. 8 To be effective, judo techniques should be applied with accuracy, with strength, velocity and power. The short bursts of energy are supplied by anaerobic metabolism while the ability to sustain the intermittent work, as well as recovery, rely on aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%